Analysis of results of catheter tip cultures in open-heart surgery patients. Issue 1 (February 1975) - Freeman, R; King, B
Abstract : A statistical analysis of 628 consecutive catheter tip cultures is presented. All were from patients undergoing open-heart surgery. The previously noted effects of early removal are shown to be significant. The possible effects of stasis, flushing, handling, and place of insertion are discussed. The unresolved significance of isolations of aerobic sporing bacilli is noted, and a decreasing incidence of postoperative infective endocarditis in the same group of patients is an encouraging sign.